Generation of induced pluripotent stem cell lines from five individuals from two families carrying a pathogenic Dutch MYBPC3 founder variant with variable degrees of hypertrophic cardiomyopathy - Floor W. van den Dolder; Vincent A.J. Warnaar; Yeszamin L. Onderwater; Annette F. Baas; Diederik W.D. Kuster; Jolanda van der Velden (Stem Cell Research)
Hypertrophic cardiomyopathy (HCM) is often caused by pathogenic or likely pathogenic variants, of which 30–50 % involve a variant in the gene encoding cardiac myosin-binding protein-C (MYBPC3). We generated human induced pluripotent stem cell lines from five individuals from two families carrying a pathogenic Dutch MYBPC3 founder variant: c.2373insG (n = 2) and c.2827C > T (n = 3), with highly variable disease expression. Peripheral blood mononuclear cells were reprogrammed using episomal plasmids. All cell lines express pluripotent markers, exhibit a normal karyotype, and could differentiate into derivatives of each germ layers in vitro. These cell lines can serve as disease model to investigate HCM pathogenesis.